Nurses long-term care leaders - Kilańska, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2010)
The subject of International Nurses Day 2010 is dedicated long-term care. Nursing on the World stands up in the next deceases before huge challenge of significant growth of is handicap and caused with diseases about chronic character, which can prevent across suitable commitment e.g. NHS. Chronic diseases usually concern in older age persons and/or weak physically. Health promotion, prevention and long-term care is closely linked to primary care that is provided primarily all in an environment of client/ patient. Nurses (as provider) increasingly take action in this range. To ensure equal benefits to all entities of the health system is necessary to use the best experience, which, with minor modifications can be adapted to suit the needs. Nursing Topics 2010; 18 (1): 72-78